2017
DOI: 10.1080/17461391.2017.1407363
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating dual careers by improving resistance to chronic stress: effects of an intervention programme for elite student athletes

Abstract: The starting point of this contribution is the potential risk to health and performance from the combination of elite sporting careers with the pursuit of education. In European sport science and politics, structural measures to promote dual careers in elite sports have been discussed increasingly of late. In addition to organisational measures, there are calls for educational-psychological intervention programmes supporting the successful management of dual careers at the individual level. This paper presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…Research in this line suggested that individuals with higher academic level usually report lower levels of well-being (Wanberg et al, 2020). Within the sports field, previous evidence relates mental health issues with higher difficulties to undertake a dual career pathway (Sallen et al, 2018;Sorkkila et al, 2020). As highlighted by other authors (e.g., Samuel et al, 2020;Stambulova et al, 2020), COVID-19 lockdown can be understood as a changeevent with unexpected demands for the athletes that combine academic and sports career.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in this line suggested that individuals with higher academic level usually report lower levels of well-being (Wanberg et al, 2020). Within the sports field, previous evidence relates mental health issues with higher difficulties to undertake a dual career pathway (Sallen et al, 2018;Sorkkila et al, 2020). As highlighted by other authors (e.g., Samuel et al, 2020;Stambulova et al, 2020), COVID-19 lockdown can be understood as a changeevent with unexpected demands for the athletes that combine academic and sports career.…”
Section: Discussionmentioning
confidence: 99%
“…This is considered a high demanding stage that requires both high personal competencies (Miró et al, 2018;Perez-Rivases et al, 2020) and a supportive environment (Morris et al, 2020). Previous research has warned about the negative consequences that a non-successful dual career might have for athletes' mental health (Sallen et al, 2018;Sorkkila et al, 2020), highlighting the need to approach this by taking a holistic approach (e.g., Wylleman and Lavallee, 2004;Wylleman, 2019) that captures both indirect (e.g., impact on life-spheres) and direct (e.g., anxiety/depression and social dysfunction) indicators of athletes' mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to this original aim, a traditional assumption in sport psychology research is that the combination of academic study and high-level sport may also involve challenges that could make athletes vulnerable to increased levels of stress (cf. Stambulova and Wylleman, 2015; Sallen et al, 2018). In the present study, the stress levels reported by the athletes were nevertheless relatively low in intensity.…”
Section: Discussionmentioning
confidence: 99%
“…With the notion of early specialisation in sport, the issues related to DC may arise even at the stage of primary school, but the likelihood will be enhanced when athletes have increasing training hours and competitions while having academic workloads in adolescence and early adulthood (Sallen, Hemming, & Richartz, 2018). As other domains related to early specialisation such as music and dance, a small number of talented young people can develop a professional level of career in the end ; they might need to make a decision on their commitment to sport, music, and dance in adolescence to accelerate their elite career path ways (Patrick, Ryan, Alfeld-Liro, Fredricks, Hruda et al, 1999).…”
Section: Introductionmentioning
confidence: 99%